Cancer Prevention and Screening for Older Adults: Part 2. Interventions to Prevent and Screen for Breast, Prostate, Cervical, Ovarian, and Endometrial Cancer. Issue 11 (3rd September 2020) - Coll, Patrick P.; Korc‐Grodzicki, Beatriz; Ristau, Benjamin T.; Shahrokni, Armin; Koshy, Alexander; Filippova, Olga T.; Ali, Imran
Abstract : The incidence of most cancers increase with age. Cancer is the second most common cause of death in older adults after cardiovascular disease. Many common cancers in older adults can be prevented from occurring or can be identified at an early stage and treated effectively. Although cancer is feared primarily because of premature mortality, for many older adults, preventing and identifying cancer in its early stages, in an attempt to reduce discomfort and disability associated with advanced cancer and cancer treatment, is also a priority. Overscreening for cancer in older adults can lead to unnecessary diagnostic testing and unnecessary treatment. Both older adults and their healthcare providers need guidance on the appropriate use of cancer prevention and screening interventions. This is the second part of a two‐part clinical review on cancer prevention and screening for adults aged 65 and older. Guidance is provided regarding the prevention and early identification of breast, prostate, cervical, ovarian, and endometrial cancer. The prevention of lung, colorectal, bladder, and kidney cancer is addressed in Part 1.